Mira Based on a Novel by Styn Streuvels - Rademakers, Fons; VanDenEnden, Edouard; VanAmmelrooy, Willeke; Decleir, Jan; VanLanckere, Carlos
Based on a novel by Styn Streuvels, which was placed on the Vatican Index in 1927, this film examines the twin difficulties of a woman and her town. The woman, a liberated sort for 1910, returns to the town her father lives in. She is not warmly welcomed by her father or her town because they believe she gives her love and her favors too freely. When she returns, she begins an affair with her uncle, who is later arrested for murder. Then she has another affair, this time with a young engineer who is building a bridge into the town. The townspeople are strongly opposed to the bridge and the change it will bring. [www.amazon.com]
Keywords: DVD-Video